Local Environment Analysis In Urban Design Studies - Hadi, Adel Said (Iraqi Journal of Architecture and Planning, 2009)
The absence of clear understanding and awareness of local urban environment analysis and its impact on urban design studies, in addition to the influence ofnew westem architectural theories and ideas, had led to the problems ofcopying and repeating urban design solutions by some professional architects and students . This paper discusses the impact of local environmental analysis in preparing efficient urban design projects. It aimes at clarifying the importance of carrying out urban environment field studies to bridge the gap between theory and practice in the urban design ideology. It presents a proposed methodology to diagnose environmental problems and to find possible solutions in the urban design projects.